AUTHENTIC MATERIAL TO IMPROVE STUDENTS’ READING COMPREHENSION AT SENIOR HIGH SCHOOL LEARNERS - SUKMAWATI SUKMAWATI SUKMAWATI (SALEE: Study of Applied Linguistics and English Education, 2020)
As value of observation in the class room the students have score 6.0. This score is as a poor category. In this research the aim is to solve this problem until the students have a good score, while the standard curriculum is 6.5. This research aimed to improve the students’ reading comprehension at eleventh grade students of SMAN 10 Makassar. This research used Classroom Action Research (CAR). The research was conducted in two cycles. Each cycle consisted of four stages that is planning, acting, observing, and reflecting stages. Data were collected through test namely multiple choices and essay. The subject of research was 32 students of SMA Negeri 10 Makassar. Authentic material was obtained by internet, magazine and newspaper. The result of the study showed that there was improvement of students’ reading comprehension after being taught by using authentic materials. There was a significant improvement of the students’ reading ability, after getting the implementation of action among 2 cycles, and the finding was 18 students (56,25 %) in the first cycle and 28 students (87,5%) in the second cycle who can pass minimum completeness criteria (KKM). Therefore, the application of authentic materials in learning and teaching process can improve the students’ reading comprehension and has reached the instruction targeted in curriculum at that school. The students are more active to participate in learning reading by applying authentic materials.